ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI RETURN SAHAM (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2011 – 2014) - Citra Fransiska, 12.05.52.0057; Wahjudi, Djoko (Students' Journal of Accounting and Banking, 2016)
The study examines the Analysis of Factors affecting the Stock Return with variable of Return On Asset (ROA), Debt to Equity Ratio (DER), Earning Per Share (EPS), Price To Book Value (PBV), and Net Profit Margin (NPM) on Stock Return. The population used is Manufacturing Company listed on the Indonesia Stock Exchange with the sampling method using purposive sampling the study period from 2011 to 2014 as many as 276. The relationship and influence between variables is described by using multiple regression analysis. The results showed that the Return On Asset (ROA) and Earning Per Share (EPS) has positive effect and significant to the Stock Return. Whereas Debt to Equity Ratio (DER). Price To Book Value (PBV), and Net Profit Margin (NPM) had no effect on Stock Return.Keywords: ROA, DER, EPS, PBV, NPM, Stock Return